Human potential [ exploring techniques used to enhance human performance - Vernon, David , 1964- (Routledge, 2009)
Throughout time, people have explored the ways in which they can improve aspects of their performance. This book examines a range of techniques that are intended to improve some aspect of performance, and examines how effective they are